1987
DOI: 10.1128/iai.55.11.2695-2700.1987
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric bacterial coaggregations involving mutans streptococci and oral actinomyces

Abstract: Mutans streptococci (MS) representing eight different serotypes were tested for their ability to coaggregate in vitro with oral actinomyces and other streptococcal species. Of the mutans streptococci tested, only strains of S. cricetus (formerly S. mutans serotype a) displayed pronounced coaggregations and only with certain strains of actinomyces. S. cricetus coaggregated, by lactose nonreversible mechanisms, with serotype 4 Actinomyces naeslundii WVU963 and WVU924 and with serotype 2 Actinomyces odontolyticus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Strain 10557 coaggregated with most A. viscosus and A. naeslundii isolates, whereas S7 did not. A. odontolytieus, which has been reported to coaggregate with few streptococcal strains (3,4), showed no difference in coaggregation with strains S7 and 10557. A. odontolyticus was also found to be ubiquitous and was present in higher numbers than both A. viseosus and A. naeslundii.…”
Section: I'orph Vroiuonas Gingivalis Atcc 33277 Atcc 25260mentioning
confidence: 88%
“…Strain 10557 coaggregated with most A. viscosus and A. naeslundii isolates, whereas S7 did not. A. odontolytieus, which has been reported to coaggregate with few streptococcal strains (3,4), showed no difference in coaggregation with strains S7 and 10557. A. odontolyticus was also found to be ubiquitous and was present in higher numbers than both A. viseosus and A. naeslundii.…”
Section: I'orph Vroiuonas Gingivalis Atcc 33277 Atcc 25260mentioning
confidence: 88%
“…Additional work is required to detemiine the molecular composition of the fimbrial tufts and how LTA tnay be exposed in these tufts in orientations that will pennit binding to both E tnwteatutn FDC 364 and B. tnatruchotii. In other intergeneric coaggregations involving Streptococcus cricetus and Actinomyces naeslundii or Actinomycis odoiitolyticus it has been suggested that LTA may play a secondary, noti-specific role by strengthening the cell-cell binding (4). Corncob fonnation between E nucleatum ATCC 10953 and S. .sanguis CC5A is also mediated by the polar fimbriae; however, the streptococcal ligand for the sttain ATCC 10953 corncob receptor is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary components have also been reported to promote intergeneric interactions between bacteria (37), and * Corresponding author. cell wall proteins have been reported to promote adherence not only to tooth surfaces but to other plaque microorganisms as well (10,29,36). Therefore, the fate of any given bacterium would depend on many conditions affecting the oral microenvironment.…”
mentioning
confidence: 99%